FINANCING PROJECTS RELATED TO THE CREATION OF RENEWABLE ENERGY SOURCES - Shaislamova Nargiza Kabilovna; Sabirova Lola Shavkatovna (European Science Publishing, 2024)
The article examines the problems and presents proposals for achieving energy security and sustainable development as a key priority for all countries of the world community. The article examines the main trends in the development of renewable energy sources in the world and in Uzbekistan, and also highlights the economic aspects of using clean energy. According to the author, in the context of global climate change and depletion of natural resources, taking into account Uzbekistan's energy dependence on supplies of extracted energy, the transition to renewable energy sources (solar and wind) will help reduce this dependence and ensure a sustainable energy future for the country, while reducing the negative impact on the environment.
Keywords: renewable energy sources, traditional energy sources, energy security, solar energy, wind energy, geothermal energy, biofuel, power units, hydroelectric power plants, “green” economy.